Empreendedorismo e startups: um estudo sobre as ações e iniciativas empreendedoras desenvolvidas na Universidade Federal do Pampa - Campus Santana do Livramento - Gonçalves, Gustavo Dorneles (2019)
This research addresses the theme of entrepreneurship and startups at universities, with the main objective to identify which actions and initiatives aimed at the dissemination of entrepreneurship exist at the Federal University of Pampa - Santana do Livramento Campus and contribute to the development of a startups entrepreneurial ecosystem, based on the vision of undergraduate students and teachers of Administration course. For this purpose, the case study was used as a method, and the interviews with teachers of the Unipampa Administration course were conducted based on a semi-structured script, as well as the application of this script in a questionnaire format open to the students of the Course. It is also worth mentioning the use of University documents and participant observation. Through content analysis it was possible to realize that currently the actions and initiatives aimed at entrepreneurship are carried out in isolation, emphasizing the need for their institutionalization. The results pointed only to the Campus Junior Company as the only project currently underway to foster entrepreneurship. Regarding the development of an entrepreneurial startup ecosystem at Campus, it was realized that its development could provide an environment that encourages creativity and innovation, but that the needs of an increase in human capital, qualification of the teachers about the theme, as well as the creation of a solid institutional policy regarding the dissemination actions of entrepreneurship at Campus.